2022
DOI: 10.5551/jat.63062
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genetic Analyses of Korean Patients with Familial Hypercholesterolemia: Results from the KFH Registry 2020

Abstract: The official journal of the Japan Atherosclerosis Society and the Asian Pacific Society of Atherosclerosis and Vascular Diseases Original Article Aims: Familial hypercholesterolemia (FH) is currently a worldwide health issue. Understanding the characteristics of patients is important for proper diagnosis and treatment. This study aimed to analyze the phenotypic and genetic features, including threshold cholesterol levels, of Korean patients with FH. Methods: A total of 296 patients enrolled in the Korean FH re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Due to gradual cost reduction, many institutes recently examine these three genes using next-generation sequencing and deletion/duplication analysis. Similar to data from other countries, copy number variations are found in approximately 10% of PV carriers, but this type of PV requires multiplex ligation-dependent probe amplification or the TaqMan method for validation [ 7 ]. When a PV is identified, it is critical to properly interpret whether it is a causative variant.…”
Section: Diagnosis Of Fhmentioning
confidence: 90%
See 4 more Smart Citations
“…Due to gradual cost reduction, many institutes recently examine these three genes using next-generation sequencing and deletion/duplication analysis. Similar to data from other countries, copy number variations are found in approximately 10% of PV carriers, but this type of PV requires multiplex ligation-dependent probe amplification or the TaqMan method for validation [ 7 ]. When a PV is identified, it is critical to properly interpret whether it is a causative variant.…”
Section: Diagnosis Of Fhmentioning
confidence: 90%
“…The Korean FH registry 2020 demonstrated that clinically diagnosed patients with FH had median total cholesterol and LDL-C levels of 306 and 221 mg/dL, respectively, and the prevalence of tendon xanthoma and CAD was 20% and 19%, respectively. Among registered patients, 60%, 36%, and 3% had a family history of severe hypercholesterolemia, premature CAD, and tendon xanthoma, respectively [ 7 ].…”
Section: Clinical and Genetic Characteristics Of Fhmentioning
confidence: 99%
See 3 more Smart Citations